Knowledge of communication disorders and the profession of speech-language therapist (SLT) among Medical and Allied Health Sciences students - Sarno, Nur Izzah; Tukiran, Nur Hanisah; Wan Ahmad, Wan Aslynn Salwani (International Islamic University Malaysia, 2024)
Background: Healthcare professionals, like doctors and allied health sciences professionals, are the first point of contact with patients. Their role involves identifying individuals with communication disorders and referring them to speech-language therapists (SLTs) for further evaluation and management. However, studies have shown a significant lack of awareness regarding the profession of SLTs among healthcare professionals. As medical and allied health sciences students represent the future healthcare workforce, assessing their understanding at the early stage is essential to ensure their comprehensive knowledge of these matters. This study aimed to investigate the knowledge of communication disorders and the profession of SLTs among medical and allied health sciences students, given the critical need to address gaps in understanding among future healthcare professionals. Methods: A cross-sectional study was conducted among 201 medical and allied health sciences students at International Islamic University Malaysia (IIUM), Pahang, Malaysia. The Knowledge and Attitude about Communication Disorders and SLT Profession among Publics (KACS-P) questionnaire was distributed using both online platforms and printed questionnaires (paper-pencil format). Results: Both groups of students demonstrated a moderate to high level of knowledge of communication disorders and the SLT profession. No significant difference in knowledge levels about communication disorders was observed between medical and allied health sciences students. Nonetheless, there was a significant difference in knowledge levels regarding the SLT profession between medical and allied health sciences students, with the latter demonstrating a superior level of understanding. The academic year does not seem to exert a noteworthy influence on these knowledge levels. Conclusion: The study provided insights into the knowledge levels of medical and allied health sciences students regarding communication disorders and the SLT profession, which is crucial for improving their curriculum content and structures to ensure comprehensive patient care in the future.